A Computational Study of Solvent and Electric Field Effects on Propylene Oxide Ring‐Opening Reaction. Issue 1 (7th January 2020) - Jin, Cheng‐Yu; Chen, Lei; Yang, Hui‐Qing; Chen, Zhao‐Xu
Abstract: Ethylene glycol (EG) is an important chemical and is widely used in the chemical industry. Hydration of ethylene oxide is a common way to produce EG. We performed density function calculations of propylene oxide (PO) ring‐opening reaction under basic, neutral and acidic conditions. We examined the influence of the solvent and electric field (EF) on the geometry, kinetics and thermodynamics of the ring‐opening. The solvent effect increases/decreases the ring‐opening barriers in the basic/neutral systems and EF exhibits significant influence on barriers and reaction heats in basic condition. All the energetic variation due to solvent and EF can be rationalized with the dipole moments of reactants, transition states, and products. Abstract : This paper presents a computational study on the propylene oxide ring‐opening reaction in the basic, neutral and acidic conditions. The solvent and electric field effects on the energy barriers and reaction heats are explored. It is revealed that the solvent and the electric field affect the thermodynamics and kinetics of the ring‐opening through the difference of the dipole moment between the reactants and transition states or products.